Revisiting 'America's Penal Experiments' 100 Years Later. (11th October 2021) - RUBIN, ASHLEY T.
Abstract: In 1921, American prison administrator and reformer, Spencer Miller, was invited to describe America's recent penal developments to the Howard League for Penal Reform. This article reviews the context of Progressive Era American prisons to better understand Miller's remarks and their lessons for prison administrators and reformers today. It briefly describes the history of American prisons into the Progressive Era as well as some developments that were most relevant to Miller, viz., the reforms at Sing Sing under famed penal reformer and warden, Thomas Mott Osborne. Next, the article reviews Miller's statement to the Howard League for Penal Reform, including his inaccurate description of prison history, which can be read as a means of emphasising the extraordinary progress made by Osborne and, implicitly, by Miller at Sing Sing and as an example to the nation. Finally, it discusses Miller's abolitionism in the context of similar discussions taking place today.